The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

VIIRS nighttime lights and geospatial constraints for monitoring commercial vitality and temporal hierarchy dynamics in Southeast Asia 2013–2024 - Run Shi; Yankai Liu; Song Liu; Xiangbin Peng; Bowen Song; Jianwei Gao; Fang Bian; Teng Zhong; Yuanzheng Cui (International Journal of Remote Sensing, 2026)

Per- and polyfluoroalkyl substances in food contact materials: Migration, health risks and sustainable alternatives - Run Li; Shensheng Xiao; Jiayong Hu; Qiao Wang; Jingguang Li; Min Fang; Nannan Qiu; Xin Liu; Yongning Wu (Trends in Food Science & Technology, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Immunotoxicity and mechanism analysis of zebrafish embryos exposure to benzothiazole and its derivatives - Wan-Ting Huang; Run-Fan Wu; Zhong-Qian Xuan; Jia-Qi Wu; Ming-Fang He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A novel multi-modal signals dynamic assessment method of idiopathic scoliosis patients for rehabilitation - Mingjie Dong; Chengyin Wang; Yinbo Chen; Yuechuan Zhang; Zhuosong Bai; Shuo Wang; Jianguo Zhang; Run Ji; Jianfeng Li; Bin Fang; Qianyu Zhuang (Medical & Biological Engineering & Computing, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

A portable slide based MIPs-FL sensor was fabricated for potential on-site detection - Run-tian Ma; Jun Zhang; Jin-xiu Guo; Fang Nian; Cheng Wang; Wei-bing Xu (Food Chemistry, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Social areas revisited through the lens of mobility: A comparative study of the traditional and mobility approaches - Run Shi; Anthony Gar-On Yeh; Fang Bian (Computers, Environment and Urban Systems, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Mechanistic Study of Jaceosidin in Regulating Secondary Inflammation After Spinal Cord Injury in Mouse by Inhibiting PKM2 Activity - Bin Dai; Zihao Fan; Rui Chen; Xuansen Weng; Run Fang (NeuroMolecular Medicine, 2025)

Strong heterogeneity in laterally exchanged particulate organic matter across tidal marshes in a large river delta - Qi Wu; Hong-Sheng Cao; Youhei Yamashita; Christian Lønborg; Run Li; Jianzhong Ge; Hualei Yang; Bolin Liu; Jinzhou Du; Fang Cao (Environmental Research, 2025)

Impact of collagen degradation on the textural quality of salmon (Salmo salar): A preliminary study from the perspective of endogenous collagenase and bacteria - Lu Sun; Run-Jian Gao; Cheng-Jian Shi; Andrew M. Hemmings; Yun-Fang Qian (Food Bioscience, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Heterotrophic nitrification-aerobic denitrification strains: An overlooked microbial interaction nexus in the anaerobic-swing-anoxic-oxic (ASAO) plug-flow system - Run-Ze Xu; Jia-Shun Cao; Song Cheng; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Journal of Environmental Management, 2025)

Characterization of β-cyclodextrin inclusion complexes embedded with lemongrass and basil essential oils and their modified sustained-release pads for large yellow croaker (Larimichthys crocea) fillet preservation - Yun-Fang Qian; Cheng-Jian Shi; Lu Sun; Run-Jian Gao; Sheng-Ping Yang (Food Bioscience, 2025)

A novel building sampling approach leveraging data mining and stratified sampling theory for energy optimization - Zhijian Fang; Lei Lei; Run Zheng (Energy and Buildings, 2025)

Synergistic effects of ether oxygen bond/benzene ring and hydrocarbon chain structure on soot morphology and nanostructure - Wenlong Dong; Run Hong; Shunjie Feng; Bingbing Qiu; Ruiming Fang; Huaqiang Chu (Fuel, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

An improved algorithm for salient object detection of microscope based on U2-Net - Yunchai Li; Run Fang; Nangang Zhang; Chengsheng Liao; Xiaochang Chen; Xiaoyu Wang; Yunfei Luo; Leheng Li; Min Mao; Yunlong Zhang (Medical & Biological Engineering & Computing, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Understanding nitrogen removal and N2O emission mechanisms in an anaerobic-swing-anoxic-oxic (ASAO) continuous plug-flow system for low C/N municipal wastewater - Run-Ze Xu; Jia-Shun Cao; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Preparation of highly hydrophobic melamine sponge for oil-water separation through copolymerization deposition - Honghui Zeng; Yuchi Zhang; Huazhong Wu; Yuansong Ye; Weiying Zhang; Run Fang (Journal of Environmental Chemical Engineering, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Circ-Bptf Ameliorates Learning and Memory Impairments via the miR-138-5p/p62 Axis in APP/PS1 Mice - Hong-Fang Wang; Yi-Bo Li; Zi-Yu Liu; Wen-Meng Xie; Qing Liu; Run-Jiao Zhang; Wen-Yu Wang; Jia-Xin Hao; Lei Wang; Dan-Dan Geng (Molecular Neurobiology, 2024)

Data-driven neural networks for biological wastewater resource recovery: Development and challenges - Run-Ze Xu; Jia-Shun Cao; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Journal of Cleaner Production, 2024)

Metagenomic investigation of antibiotic resistance genes and resistant bacteria contamination in pharmaceutical plant sites in China - Run-Dong Zhang; Fang-Zhou Gao; Yi-Jing Shi; Jian-Liang Zhao; You-Sheng Liu; Liang-Ying He; Guang-Guo Ying (Environmental Pollution, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Mixotrophic denitrification of waste activated sludge fermentation liquid as an alternative carbon source for nitrogen removal: Reducing N2O emissions and costs - Fang Fang; Jie Yang; Ling-Long Chen; Run-Ze Xu; Jing-Yang Luo; Bing-Jie Ni; Jia-Shun Cao (Journal of Environmental Management, 2024)

Cytogenetic analysis reveals a mechanism of compatibility in distant hybridization between tree peony and herbaceous peony - Yuan Zhong; Ming-jie Du; Run-ze Ji; Qi Rong; Zi-heng Guan; Fang-yun Cheng (Euphytica, 2024)

Study on indoor thermal perception, behavioral adaptation in late pregnancy and their effects on adverse birth outcomes in south China - Jie Ni; Huailin Wang; Xinyue Yu; Run Gao; Yanqiu Li; Zhaosong Fang; Jason Kai Wei Lee; Zhenghong Zhu; Maimaitiminjiang Wulayin; Xin Chen; Cunrui Huang; Qiong Wang (Building and Environment, 2024)

Distinct North American teleconnection of the strong El Niños as modulated by the ENSO-annual cycle combination mode - Minghong Liu; Hong-Li Ren; Fang Zhou; Run Wang (Climate Dynamics, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

The role of the gut-liver axis in modulating non-alcoholic fatty liver disease through dietary patterns and microecological agents - Yucheng Fang; Ziyang Fang; Ziwei Li; Run Yu; Haimeng Zhang; Qinwen Wang; Xiangrong Cheng; Guowei Le; Guoqing Wu (Food Bioscience, 2023)

Phosphorus recovery from synthetic anaerobic fermentation supernatant via vivianite crystallization: Coupling effects of various physicochemical process parameters - Jia-Shun Cao; Su-Na Wang; Run-Ze Xu; Jing-Yang Luo; Bing-Jie Ni; Fang Fang (Science of The Total Environment, 2023)

Cytotoxic lanostane-type triterpenes from the fruiting bodies of Ganoderma lucidum - Xiu-run Huang; Fang Cai; Jing Chen; Chang-hui Wu; Ye Li; Jian-hua Xu; Peng Li (Natural Product Research, 2023)

Chitosan-Urushiol nanofiber membrane with enhanced acid resistance and broad-spectrum antibacterial activity - Xiaoyu Jie; Bing-Chiuan Shiu; Yuchi Zhang; Huazhong Wu; Yuansong Ye; Run Fang (Carbohydrate Polymers, 2023)

Comprehensive analysis of arachidonic acid metabolism-related genes in diagnosis and synovial immune in osteoarthritis: based on bulk and single-cell RNA sequencing data - Bizhi Tu; Run Fang; Zheng Zhu; Guang Chen; Cheng Peng; Rende Ning (Inflammation Research, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Emission characteristics, risk assessment and scale effective control of VOCs from automobile repair industry in Beijing - Hailin Wang; Run Hao; Xiaoqi Xie; Guoao Li; Xinxin Wang; Wenqing Wu; Huan Zhao; Zhongshen Zhang; Li Fang; Zhengping Hao (Science of The Total Environment, 2023)

Leading modes of Asian–Australian monsoon interannual variability as represented in CMIP5 models - Fang Zhou; Hong‐Li Ren; Ming‐Hong Liu; Run Wang; Kai Huang (International Journal of Climatology, 2021)
The Asian–Australian monsoon (AAM) exerts a strong impact on the regional climate. The ability of climate models to simulate the AAM is of great importance. This study evaluates the performance of 26 models, which participate in the Coupled Model Intercomparison Project phase 5 (CMIP5), in representing features of the leading modes of the AAM interannual variability. This is achieved by diagnosing quantitative metrics derived from a Season‐reliant Empirical Orthogonal Function (S‐EOF) analysis, and plausible external forcing contributing to the simulation results are presented. Our results show that the CMIP5 models can generally capture the spatial patterns of the leading modes of AAM interannual variability during El Niño development periods because of strong air–sea interactions. The variance percentage explained by the first two S‐EOF modes is found to be closely related to the amplitude of the El Niño‐Southern Oscillation (ENSO) in the models. In contrast, simulation of the periodicity remains challenging, and the models show deficiencies in the accurate capture of periodic characteristics. Models with realistic ENSO simulations typically perform well in simulating S‐EOF1, and the key to improving the simulation of S‐EOF2 is the greater intensity of the simulated field of background heating over the Northwest Pacific warm pool. The multimodel ensemble (MME) performs better than most of the 26 individual models. Models in the MME with better ENSO simulation and stronger warm pool heating are found to be better able to represent the relationships between the first two leading S‐EOF modes and ENSO, although biases remained.

Seismic risk evaluation for a planning mountain tunnel using improved analytical hierarchy process based on extension theory - Jing-song Xu; Hua Xu; Run-fang Sun; Xiang-wei Zhao; Yin Cheng (Journal of Mountain Science, 2020)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Spatial patterns of interprovincial mountain geographical names in China and implications for regional governance - Sheng-rui Zhang; Ying-jie Wang; Hong-run Ju; Tong-yan Zhang; Dai-chao Li; Lei Fang; Ying-ying Wang (Journal of Mountain Science, 2018)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Deep-seated large-scale toppling failure in metamorphic rocks: a case study of the Erguxi slope in southwest China - Ming Liu; Fang-zhou Liu; Run-qiu Huang; Xiang-jun Pei (Journal of Mountain Science, 2016)

Cyclic load testing of pre-stressed rock anchors for slope stabilization - Da Zheng; Fang-zhou Liu; Neng-pan Ju; J. David Frost; Run-qiu Huang (Journal of Mountain Science, 2016)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

Effects of exogenous hydrogen sulfide on the ascorbate and glutathione metabolism in wheat seedlings leaves under water stress - Chang-juan Shan; Sheng-li Zhang; Dong-fang Li; Yuan-zeng Zhao; Xue-liang Tian; Xin-liang Zhao; Ying-xia Wu; Xiu-ying Wei; Run-qiang Liu (Acta Physiologiae Plantarum, 2011)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)